Investigation of association between CD40 current gene variants (rs4810485, rs1883832 and rs3765459) and serum CD154 protein levels in Iranian migraineurs - Ramroodi, Norullah; Saboori, Hadi; Sanadgol, Nima (Cellular and Molecular Biology, 2018)
Migraine is a chronic neurological disease described by recurrent moderate to severe headaches often in association with neuro-inflammation. As cytokines are affect the immune response and migraine exacerbation, the current study aimed to investigate the possible associations between CD40 polymorphisms and level of soluble CD154 protein with migraine. In a prospective case-control study, we studied blood samples of 190 patients with migraine (migraineurs) and 200 healthy controls (HCs) from southeast Iran. Genotyping for the CD40 (rs4810485-intron, rs1883832-5´-UTR, and rs3765459-intron) gene variants were executed using PCR-RFLP and soluble CD154 protein levels were measured via ELISA method. Among CD40 gene variants, rs1883832 (TC genotype) was significantly associated with migraine (P = 0.007, OR = 2.326, 95% CI = 1.258-4.303).  No significant associations observed between the rs4810485 and rs3765459 SNPs with migraine. The most frequent genotypes for CD40 were GG in rs4810485 (51.5%) and rs3765459 (62.1%) as well as TC in rs1883832 (53.7%). There was no statistically relationship between these gene variants and different subclasses of migraine. Concentration of soluble CD40L among patients with rs1883832 (TC genotype) were significantly (P = 0.027, OR = 0.417, CI = 0.192-0.906) higher in compared to healthy controls. Our findings showed that in CD40 rs1883832, TC genotype may have a role in migraine susceptibility. Therefore, it suggested that in addition to other factors, CD40 rs1883832 (TC genotype) genetic variation may also play a critical role in the etiology of migraine.